Jens Bircherod's In Timaeum exercitatio historico-philologico-philosophica (1682): Platonic cosmology in seventeenth-century Denmark. Issue 4 (8th August 2019) - Claessens, Guy
ABSTRACT: This article examines a previously unstudied dissertation on Plato's Timaeus presumably authored by the Danish bishop Jens Bircherod (1658–1708). By means of a study of Bircherod's sources and interpretative method, it assesses the place of his In Timaeum exercitatio historico-philologico-philosophica (1682) in the history of philology and philosophy, and in the context of seventeenth-century Lutheran pedagogy. It shows how Bircherod makes use of Plato's dialogue against the background of early modern religious debates, and how his method largely follows the historicist approach that had begun to characterise the reception history of the Timaeus since the late sixteenth century. It argues that Bircherod wrote his historical-philological-philosophical exercise on the Timaeus to demonstrate the existence of divine providence and monotheistic tendencies in antiquity, and to harness Plato's cosmological treatise to the cause of Christian apologetics.